Role of miRNAs shuttled by mesenchymal stem cell-derived small extracellular vesicles in modulating neuroinflammation - Debora Giunti (Nature Portfolio, 2021)
Abstract Mesenchymal stromal/stem cells (MSCs) are characterized by neuroprotective, immunomodulatory, and neuroregenerative properties, which support their therapeutic potential for inflammatory/neurodegenerative diseases, including multiple sclerosis (MS) and amyotrophic lateral sclerosis (ALS). One mode of action through which MSCs exert their immunomodulatory effects is release of extracellular vesicles that carry proteins, mRNAs, and microRNAs (miRNAs), which, once transferred, modify the function of target cells. We identified nine miRNAs significantly dysregulated in IFN-γ-primed MSCs, but present at different levels in their derived small extracellular vesicles (s-EV). We show that miR-467f and miR-466q modulate the pro-inflammatory phenotype of activated N9 microglia cells and of primary microglia acutely isolated from late symptomatic SOD1G93A mice, a murine ALS model, by downregulating Tnf and Il1b expression. Further analysis of the mode of action of miR-467f and miR-466q indicated that they dampen the pro-inflammatory phenotype of microglia by modulating p38 MAPK signaling pathway via inhibition of expression of their target genes, Map3k8 and Mk2. Finally, we demonstrated that in vivo administration of s-EV leads to decreased expression of neuroinflammation markers in the spinal cord of EAE-affected mice, albeit without affecting disease course. Overall, our data suggest that MSC-derived exosomes could affect neuroinflammation possibly through specific immunomodulatory miRNAs acting on microglia.